The impact of physiological load on anticipation skills in badminton: From testing to training - Alder, D. B.; Broadbent, D. P.; Stead, J.; Poolton, J. (Journal of Sports Sciences, 2019)
Research remains unclear on the impact of physiological load on perceptual-cognitive skills in sport. Moreover, no study has examined the training of perceptual-cognitive skills under physiological load. The current study comprised two phases. Firstly, we examined the impact of badminton-specific physiological load on anticipatory skills in expert badminton players (n = 13), including key underlying mechanisms, such as gaze behaviour. Under high physiological load, participants displayed less efficient visual search behaviour and showed a reduction in response accuracy. Secondly, we examined the effects of combining perceptual-cognitive simulation training with the high physiological load. Ten of the expert badminton players were assigned to a combined training group, where the simulation training and the physiological load intervention occurred simultaneously or an independent training group, whereby the two components were completed independently. The combined training group showed a positive change in the efficiency of their visual search behaviours compared to the independent training group, but no significant performance improvements were found. Overall, findings demonstrate that high physiological load is detrimental to experts` anticipatory skills. However, combining perceptual-cognitive simulation training with high physiological load can potentially negate these debilitating effects.